Assessment of Essay Quiz System in the LMS VidyaNusa Framework Using the Nazief and Adriani Stemming Algorithms - Ratih Kusuma Dewi (Journal of Information Technology and Its Utilization, 2019)
Learning evaluation is very important for students to know the level of understanding of a material that has been given. Evaluation can be done by giving an exam or test. The type of exam can be multiple choice, matching, right or wrong, short answer, description answer. This study focuses on the essay quiz assessment system in the LMS VidyaNusa framework using Nazief and Adriani algorithms. The stemming algorithm is a word cutting process that makes use of basic words using certain rules. The stemming process is carried out for Indonesian-language texts which generally consist of a combination of prefixes, basic words and suffixes. This Nazief and Andriani algorithm will be processed in real time. This system will help the teacher in the assessment of answers to student essay quiz because this system is equipped with value weighting so that it reduces subjective assessors and increases accuracy in assessment.